Occurrence and genetic characteristics of Cryptosporidium spp. and Enterocytozoon bieneusi in pet red squirrels (Sciurus vulgaris) in China - Deng, Lei (Sci Rep, 2020)
Cryptosporidium spp. and Enterocytozoon bieneusi are two well-known protist pathogens which can result in diarrhea in humans and animals. To examine the occurrence and genetic characteristics of Cryptosporidium spp. and E. bieneusi in pet red squirrels (Sciurus vulgaris), 314 fecal specimens were collected from red squirrels from four pet shops and owners in Sichuan province, China. Cryptosporidium spp. and E. bieneusi were examined by nested PCR targeting the partial small subunit rRNA (SSU rRNA) gene and the ribosomal internal transcribed spacer (ITS) gene respectively. The infection rates were 8.6% (27/314) for Cryptosporidium spp. and 19.4% (61/314) for E. bieneusi. Five Cryptosporidium species/genotypes were identified by DNA sequence analysis: Cryptosporidium rat genotype II (n = 8), Cryptosporidium ferret genotype (n = 8), Cryptosporidium chipmunk genotype III (n = 5), Cryptosporidium rat genotype I (n = 4), and Cryptosporidium parvum (n = 2). Additionally, a total of five E. bieneusi genotypes were revealed, including three known genotypes (D, SCC-2, and SCC-3) and two novel genotypes (RS01 and RS02). Phylogenetic analysis revealed that genotype D fell into group 1, whereas the remaining genotypes clustered into group 10. To our knowledge, this is the first study to report Cryptosporidium spp. and E. bieneusi in pet red squirrels in China. Moreover, C. parvum and genotype D of E. bieneusi, previously identified in humans, were also found in red squirrels, suggesting that red squirrels may give rise to cryptosporidiosis and microsporidiosis in humans through zoonotic transmissions. These results provide preliminary reference data for monitoring Cryptosporidium spp. and E. bieneusi infections in pet red squirrels and humans.